The social value of music during the COVID-19 pandemic: exploring the benefits of online music participation for social capital, education, belonging and wellbeing - Krüger Bridge, Simone ca. 20./21. Jh. (Journal of beliefs and values, 2023)
This article presents the findings of The Digital Turn research project (2020–2021) that sought to understand, via qualitative research, the social value of online music participation offered by Liverpool Cathedral during the COVID-19 pandemic. The article will establish the context for the study, followed by the research methods for data collection and analysis, and the presentation and discussion of the results, which are grouped along four themes: Social Capital, Education, Belonging and Wellbeing. The results show that online music participation during the COVID-19 pandemic enhanced people’s sense of social connectedness and belonging; provided important opportunities for formal and informal music education and learning and exposure to an eclectic range of musical styles; resonated with and reinforced participants’ sense of shared identity and belonging; and enhanced people’s general health and wellbeing, along with a sense of normality and routine. The article will conclude with the study’s limitations and vision for future research.